How are we alike? Language and ethnicity as determinants of similarity in three ethnic groups - Norvilas, Algis; Valskytė-Janušaitienė, Ieva (Psichologija, 2007)
This study asked the question: what role do language and ethnic-cultural background play in perception of similarity amongst members of three ethnic groups: Lithuanians, Russians, and Poles in Vilnius, Lithuania. Based on the results of the classic studies of Taylor et al. (1973) and Giles et al. (1976) it was predicted that language would have a powerful consolidating effect on each respective ethnic group, but especially the two minority groups: Russians and Poles. Ethnic-cultural background would also draw people closer together, but less visibly so. It was also expected that the two factors would show interaction. Forty Lithuanian students from Vilnius University and 25 of each Lithuanian, Russian, and Polish students from Vilnius area high-schools participated in the study. The groups were about evenly divided in terms of gender. The study utilized the methodological technique of multidimensional scaling (MDS). The participants were first presented with labels (descriptions) of people living in Lithuania. The labels incorporated reference to one of three ethnic groups (Lithuanians, Russians, and Poles) and one of three spoken languages (Lithuanian, Russian, and Polish). Crossing the three ethnic descriptions with the three languages produced nine labels (e.g., A Pole living in Lithuania who speaks Russian, A Lithuanian living in Lithuania who speaks Polish, etc.), to which the label MYSELF, a reference to one’s own person, was added to serve as an anchor point in relation to the other labels. All told, then, the participants were exposed to ten labels. After viewing the labels, the participants were given a booklet in which the ten labels were presented as pairs in all possible combinations (e.g., A Lithuanian living in Lithuania who speaks Lithuanian: A Russian living in Lithuania who speaks Lithuanian, etc.). This time they were asked to leaf through the booklet and to evaluate each of the paired labels for their degree of similarity by circling the appropriate value on a nine-point rating scale. The value of one signified that the paired labels were “very different”, and nine that they were “very similar”. The results were analyzed by first computing the mean similarity values for each of the paired label combinations. The resulting matrix of mean values was then subjected to an MDS analysis. In the case of Lithuanian participants, it is clear that language exerts a potent effect on drawing people closer together. Not only did the participants see other Lithuanians who spoke Lithuanian as being very similar to them, but they also saw Russians and Poles who spoke Lithuanian as moving in their direction. Overlap in ethnicity likewise enhanced the experience of similarity, but this was only true for high-school students. There is also noticeable interaction such that, for instance, the same language might draw Russians and Poles towards the Lithuanian side, but their different ethnicity would still keep them at bay. The results for the Polish participants were similar to those of the Lithuanian group, but only selectively so. They also perceived language and ethnicity as enhancing the experience of similarity, but this occurred only in relationship to the Lithuanian group. They saw Russians in terms of both language and ethnicity as essentially similar to themselves. The Russian participants present a more complex picture. The Russian men and women showed different reaction patterns to the role of language and ethnicity. Generally, Russians seem to place greater emphasis on ethnicity than language as a binding variable. Otherwise, their response patterns were marked by pervasive interaction.
Keywords: language; ethnicity; ethnic identity